Autobiographical records and the sociological craftsmanship of Slam resistance in Sociology teaching (Simbiótica. Revista Eletrônica, 2024)
This research presents ways to enhance the teaching of Sociology with the aim of sharing advances, challenges and results of pedagogical actions at the heart of the conception of sociological craftsmanship. Faced with the challenge of advancing the traditional conceptions and practices of encyclopedic and boring classes, both in school and university contexts, we establish new standards of mobilizing potential in the teaching of Sociology. Pedagogical resources focused on the use of autobiographical records, added to the movement of meaning of knowledge through the creation and reciting of poetry with the use of Slam resistance, within a theoretically based pedagogical perspective, it was possible to identify educational advances contained in these new teaching methodologies of Sociology. Building living forms of knowledge in the teaching space, capable of relating students' lives with sociological knowledge, later transformed into poems narrated and verbalized in public spaces constitutes the challenge materialized in this research.
Keywords: Teaching Sociology; School Sociology; autobiography; slam resistance; sociological crafts